Ernest Hunter: Aboriginal Health and History: Power and Prejudice in Remote Australia - Bang, Hanne (Tidsskriftet Antropologi, 1994)
Ernest Hunter: Aboriginal Health and History: Power and Prejudice in Remote Australia Anmeldes af Hanne Bang